1992
DOI: 10.1111/j.1365-2710.1992.tb01299.x
|View full text |Cite
|
Sign up to set email alerts
|

A survey of prescription label preferences among community pharmacy patrons

Abstract: Fifty-five randomly selected community pharmacy patrons were surveyed regarding their preferences between four different prescription labels. The variables displayed on the four labels were: (i) laser printed, (ii) dot-matrix printed, (iii) glossy surface, and (iv) matt surface. The study population was stratified by age and gender. Statistical analysis of the results indicated a clear preference by all groups for the laser printed labels (P less than 0.001), and the only other statistically significant findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…First, from a functional perspective, the preference for glossy might be reduced as it interferes with readability. For instance, a survey of prescription label preferences among community pharmacy patrons revealed that a glossy surface is not recommended since it makes the label less legible (Luscombe, Jinks, & Duncan, 1992). Similarly, given the fact that gloss is the shiny surface appearance created when light is reflected from that surface (e.g., Hunter, 1975; Obein, Knoblauch, & Viénot, 2004; Smith, 1999), it is unclear whether a glossy surface finish would still be preferred in conditions of under‐ or overexposure of light.…”
Section: Discussionmentioning
confidence: 99%
“…First, from a functional perspective, the preference for glossy might be reduced as it interferes with readability. For instance, a survey of prescription label preferences among community pharmacy patrons revealed that a glossy surface is not recommended since it makes the label less legible (Luscombe, Jinks, & Duncan, 1992). Similarly, given the fact that gloss is the shiny surface appearance created when light is reflected from that surface (e.g., Hunter, 1975; Obein, Knoblauch, & Viénot, 2004; Smith, 1999), it is unclear whether a glossy surface finish would still be preferred in conditions of under‐ or overexposure of light.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, one study looked at printer style and print finish of general pharmacy labels. 27 Again, although this study was conducted on non-health care professionals, there is no evidence to suggest that it cannot be generalized to the health professional community. In this study, all groups preferred laser-generated labels to dot matrix printer labels.…”
Section: Discussionmentioning
confidence: 92%
“…In total, 21 documents met the eligibility criteria for this systematic review. 4,[8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]…”
Section: Literature Search and Environmental Scan Resultsmentioning
confidence: 99%
See 1 more Smart Citation